The effect of forest plantation projects on the livelihood of forest-fringe communities in Northern Region of Ghana (A case study in Kenikeni and Yirada Forest Reserves) - Vifa, Isaac Kofi (2013)
A Thesis Submitted to the School of Graduate Studies, Kwame Nkrumah University of Science And Technology, Kumasi in partial fulfillment of the requirements for the award of Degree of Master of Science in Agroforestry, 2011.